Letter from Kasimir Fajans to Georg Bredig, July 11, 1937 - Fajans, Kasimir (1937)
Letter from Kasimir Fajans (1887-1975) to Georg Bredig (1902-1944). Fajans tells Georg that he has found a job in the United States for Max Albert Bredig (1902-1977), Georg's son. The position is at the University of Michigan in Ann Arbor. Fajans tells Bredig about the Department of physics at Ann Arbor and his summer activities. He ends the letter requesting that if Max does not take the position, that Georg recommend another candidate.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Fajans, Kasimir, 1887-1975; University of Michigan; Jews